ANALISA LINK BUDGET KOMUNIKASI PELABUHAN KE KAPAL MENGGUNAKAN KANAL VHF - Sherli D. J Sherli D. J; Laode M. A Laode M. A; Hani’ah M Hani’ah M; Ari W Ari W; Okkie P Okkie P; Nur Adi S (SENTIA 2016, 2016)
Indonesia is a maritime nation which consists of approximately 78,86% ocean territory and become one of the highest shipping traffic in Southeast Asia. Therefore, it requires an integrated system to enable traffic entry and exit communication of oceangoing vessels in the port. Tanjung Perak Port has classified as high-traffic port resulting in high communication traffic. The objective of this research is to observe propagation model that established by transmitter and receiver. Maritime radio communication is required to send ships location and other mandatory information for emergency case. Generally, maritime communication has been implemented by utilizing VHF communication systems, but not every part of the sea has a good signal coverage and quality. In this study, some input and output parameters of VHF are necessary to calculate link budget, such as pathloss, acceptance, fade margin, and etc. The propagation characteristics affect the quality of the received power and coverage area. The reduction percentage of received power in distance is 7,63%, whereas the effect of losses on a coverage area that is 12,5%, as same as the cable attenuation.